IMPLEMENTASI METODE DESIGN THINKING DALAM PERANCANGAN UI/UX PADA TAMPILAN WEBSITE DAN MOBILE - Ilham Takbir Al Azhiim; Vera Rizki Yuniar (Prosiding Seminar Nasional Indonesia, 2026)
This study discusses the implementation of the Design Thinking method in UI/UX design in two digital product contexts, namely information system websites and mobile applications. The focus of the research is directed at the use of Design Thinking as a human-centered design framework, rather than on testing instruments or detailed feature discussions. This study uses a mapping of the design process of the main Design Thinking activities, namely understanding users, formulating problems, developing solution ideas, creating prototypes, and making design improvements based on feedback. The results of the discussion show that Design Thinking provides a systematic yet flexible workflow in translating user problems into UI/UX designs. In the website context, this method emphasizes information architecture, navigation hierarchy, and workflow organization. In the mobile context, this method emphasizes concise interaction flows, visual clarity, and simplicity of use. Thus, Design Thinking can be applied adaptively in website and mobile UI/UX design.